Differential susceptibility effects of oxytocin gene (OXT) polymorphisms and perceived parenting on social anxiety among adolescents. (13th June 2017) - Olofsdotter, Susanne; Åslund, Cecilia; Furmark, Tomas; Comasco, Erika; Nilsson, Kent W.
Abstract: Social anxiety is one of the most commonly reported mental health problems among adolescents, and it has been suggested that parenting style influences an adolescent's level of anxiety. A context-dependent effect of oxytocin on human social behavior has been proposed; however, research on the oxytocin gene ( OXT ) has mostly been reported without considering contextual factors. This study investigated the interactions between parenting style and polymorphic variations in the OXT gene in association with social anxiety symptoms in a community sample of adolescents ( n = 1, 359). Two single nucleotide polymorphisms linked to OXT, rs4813625 and rs2770378, were genotyped. Social anxiety and perceived parenting style were assessed by behavioral questionnaires. In interaction models adjusted for sex, significant interaction effects with parenting style were observed for both variants in relation to social anxiety. The nature of the interactions was in line with the differential susceptibility framework for rs4813625, whereas for rs2770378 the results indicated a diathesis–stress type of interaction. The findings may be interpreted from the perspective of the social salience hypothesis of oxytocin, with rs4813625 affecting social anxiety levels along a perceived unsafe–safe social context dimension.